Attenuation of hepatic and breast cancer cells by Polygonatum verticillatum embedded silver nanoparticles. (November 2020) - Pathak, Manish; Pathak, Prateek; Rimac, Hrvoje; Grishina, Maria; Bagale, Uday; Kumar, Vikas; Rahul Majee; Vladimir Potemkin; Verma, Amita
Abstract: The aim of the current research was to investigate the anti-hepatic and anti-breast cancer activity of Polygonatum verticillatum rhizome extract embedded silver nanoparticles ( Pv- AgNPs). The addition of AgNO3 (1 mM) in the process of synthesis, showed change in color of the rhizome extract from brown to dark brown, suggested the formation of silver nanoparticles. Further, FTIR spectra of Pv -AgNPs showed polyphenolic vibrational peaks of hydroxyl groups (3734 - 3367 cm −1 range) that are responsible for the stabilization of nanoformulation. SEM, TEM, EDX, and XRD analysis showed that nanoparticles contain spherical shape, irregular size and well dispersed throughout the plane. Whereas, the elemental analysis results confirmed that 93.28% of Ag ions were present in the formulation. In-vitro anticancer evaluation showed that Pv- AgNPs (86.58 ± 0.84–46.17 ± 1.27% cell viability) have dose-dependent inhibition potency against HepG-2 and MCF-7 cancer cells lines. The comparison study also suggested that Pv -AgNPs consist higher anticancer efficacy than rhizome extract. Computational ADMET and topoisomerase activity prognosis showed optimal drug like properties of major phyto-compounds, which were adsorbed on the surface of silver during the synthesis of nanoformulation. Docking and molecular dynamics simulation study confirmed that the selected phyto-compounds anthraquinones, diosgenin, 5-hydroxymethyl-2-furaldehyde, and santonin have strong tendency to interact with the topoisomerase enzyme. The overall computational studies illustrated that phyto-compounds have mild tendency to act as anticancer agents but the experimental assay showed that in a combination such as whole extract of rhizome and Pv -AgNPs possessed significant potency against the breast and hepatic cancer. Graphical abstract: Image 1 Highlights: Green synthesis of Polygonatum verticillatum embedded silver nanoparticles. P. verticillatum embedded AgNPs showed significant activity against breast and liver cancer cell lines. Evaluation of nontoxic effect of nano-formulation on two non-cancerous cell lines showed nontoxic to normal cells. Major phyto-compounds of the selected plant rhizome showed optimal ADMET properties. Molecular dynamics study showed that majority of phyto-compounds have tendency to bind on same binding pocket.